Pesticide Safety Around Animals - Phillip E. Kaufman; Emma N. I. Weeks (EDIS, 2013)
In general, infested animals are unhealthy and cannot be managed efficiently, so pesticides are commonly used to protect animals from pests. The successful control of pests requires careful mixing and application of recommended pesticides according to label directions. Besides ensuring the control of pests, applying pesticides at the recommended rate is necessary to prevent injury to the animal. This 5-page fact sheet was written by P. E. Kaufman and E. N. I. Weeks and published by the UF Department of Entomology and Nematology, October 2012.